Effects of sound absorbing facades on the acoustical quality in different simulated inner courtyard situations - Eggenschwiler Kurt; Jansohn Tilljan; Blau Matthias; Schäffer Beat (Acta Acustica)
Residential perimeter blocks can shield traffic noise, but the acoustical quality may be sub-optimal in the inner courtyards. This study investigated how effective sound-absorbing facade surfaces and balcony soffits as well as an absorbing floor (lawn) influence the acoustical quality in inner courtyards. Room acoustical simulations were carried out for eight generic and two real-world models with very large numbers of transmission paths. Facades (reflecting, fully absorbing, partially absorbing), balcony soffits (reflecting, absorbing) and courtyard floor (reflecting, absorbing) were varied. A range of room acoustical parameters were evaluated, namely, reverberation time T20, early decay time EDT, strength G, speech transmission index STI, and Dietsch’s echo criterion EK. The simulations revealed that fully absorbing facades are an effective measure to improve the acoustical quality in inner courtyards, while partially absorbing facades result in smaller improvements. In fact, each additional storey of absorbing facades further improves the situation. In the case of non-absorbing facades, absorbing balcony soffits or an absorbing floor in the inner courtyard are not very effective as individual measures and may even increase disturbances due to echoes. The same holds true for situations with absorbing facades. Their feasibility should therefore be clarified for the individual situation in question.